The Prevalence of Scoliosis Screening Positive and Its Influencing Factors: A School-Based Cross-Sectional Study in Zhejiang Province, China - Zou, Yan; Lin, Yun; Meng, Jia; Li, Juanjuan; Gu, Fang; Zhang, Ronghua (Frontiers in Public Health, 2022)
Objective: Early detection of scoliosis is of great significance to patients with scoliosis and the whole society. This paper aims to learn the prevalence of scoliosis screening positive among students in primary and secondary schools, and to explore the influencing factors. Methods: In 2019, a stratified cluster sampling technique was employed in this school based cross-sectional study. Sampling covers all prefecture level cities in Zhejiang Province. Based on the whole class, at least 80 students in each grade of primary school, junior high school and senior high school were selected. Physical examination and scoliosis screening were performed in the school-based investigation. Distribution of demographic characteristics and nutritional status of children and adolescents with scoliosis screening positive were explored. Results: A total of 45547 students were screened. The overall prevalence of children and adolescents with scoliosis screening positive were 3.9%. Higher prevalence of scoliosis screening positive was found in students living in urban area (4.1%), female students (4.1%), students with low weight (5.3%) (p < 0.05), and the prevalence increased with age (p < 0.05). In logistic analysis, we found age (OR=1.145; 95% CIs:1.128, 1.162), gender (OR=1.118; 95% CIs:1.016, 1.230) and low weight (OR=1.480; 95% CIs:1.250, 1.751) were the influencing factors for prevalence of scoliosis screening positive (p < 0.05). Conclusions: There were no disparities between living areas, but there was significant difference between genders, among different ages, and among different nutritional status of children and adolescents with or without scoliosis screening positive. In multi analysis, age, gender, and low weight were the influencing factors for prevalence of scoliosis screening positive. Age and gender specific scoliosis screening strategy and nutritional public health policies for children and adolescent are need.